Compositional, optical and electrical characteristics of SiOx Thin films deposited by reactive pulsed DC magnetron sputtering - Carneiro, Joaquim O. (2019)
The influence of O2 flow rate on the compositional, optical and electrical characteristics of silicon oxide (SiOx) thin films (x < 2) were studied in this work. The SiOx thin films were obtained by pulsed direct current (DC) magnetron sputtering (PMS) onto n-type Si wafers (and also on glass substrates) at a vacuum of 3 × 10−3 Pa. Rutherford backscattering spectrometry (RBS) was used to check the compositional elements of deposited films and its oxidized states were analysed via Fourier-transform infrared (FTIR) spectroscopy. The optical properties of as-deposited SiOx thin films were investigated from transmittance measurements at room temperature in the wavelength range of 250–800 nm. The obtained data reveal that the Urbach energy (a measure of the band tail extension, Eu) decreased from about 523 to 172 meV as the rate of oxygen gas flow increased. On the contrary, the optical energy band-gap (Eg) increased from 3.9 to 4.2 eV. Conduction and valance band positions (relative to the normal hydrogen electrode) were also evaluated. The observed behavior is probably associated with the degree of disorder and defects presented in the as-deposited SiOx thin films, probably due to the presence of newly inserted oxidized OnSiHy species resulting from some contamination with water vapor desorbed from the walls of the deposition vacuum chamber. After deposition of a gold top electrode, the electrical characteristics of the fabricated Au/SiOx/n-Si system (i.e., a metal/insulator/semiconductor structure—MIS) were studied via characteristic I-V curves and their dependence upon the O2 flow rate are reported. It was observed that the Au/SiOx/n-Si structure behaves like a Schottky-diode exhibiting a very good diode rectifying performance with a rectification ratio of at least 300 and up to 104, which refers to the samples produced with the lower and higher O2 flow rates, respectively. It was also found that the O2 flow rate influences the rectifying performance of the SiOx/n-structures since both the diode ideality factor, n, and the diode series-resistance, RS decreases with the increase of O2 content, possibly reflecting a closer approximation to a full stoichiometric condition.